The 7 principles of conflict resolution : how to resolve disputes, defuse difficult situations and reach agreement - Weinstein, Louisa (Pearson, 2018)
7 Principles of Conflict Resolution is the go-to resource for conflict and dispute resolution, whether you're new to the subject or an experienced practitioner.